NeuroStratE: An educational neuroscience intervention to reduce procrastination behavior and improve executive planning function in higher students - Cherrier, Sophie; Wattelez, Guillaume; Ferrière, Séverine; Borst, Grégoire (Frontiers in Education, 2023)
This study aimed to evaluate the impact of an educational cognitive neuroscience intervention (NeuroStratE) focusing on teaching the functioning of the brain and practical tools to address the procrastination behavior of 199 students enrolled at university from 2019 to 2021. The evolution of procrastination behavior is measured by specific scales and the planning ability through the Tower of Hanoi test. We compared the change in procrastination behaviors and planning ability between the pre and post-test to those of a control group. Procrastination behavior reduction and planning ability improved more in the students who followed the intervention (N = 179) than those in the control group (N = 20). Using mixed methods, these results were qualitatively refined with student feedback on the value of the intervention program, along with individual student interviews. This study highlights that it is particularly courses of procrastination and associated practical tools which contributed to reduced procrastination behavior and improved the planning ability.